Ageing with HIV: Psychological and Functional Wellbeing and its biopsychosocial determinants at the Kenyan coast - Mwangala, Patrick Nzivo (University of the Witwatersrand, Johannesburg, 2024)
Background: Kenya, and sub-Saharan Africa (SSA) in general, are experiencing rapid demographic transitions, including the ageing of the HIV population. Intuitively, this has created a subgroup of vulnerable older adults living with HIV (OALWH) requiring an urgent response in research, policy, and programming to mitigate their complex and transitioning needs. Existing evidence on HIV and ageing, largely from European cohort studies, demonstrates that OALWH are vulnerable to ill health, especially psychological morbidities (e.g. mental and cognitive impairments), geriatric syndromes (e.g. frailty) and multimorbidity. For the last decade, the SSA region has witnessed noteworthy progress in ageing and health, e.g. the establishment of health and ageing cohorts in South Africa. Yet, current evidence on mental, cognitive, and geriatric syndromes among OALWH is inadequate from the region partly because of heterogeneous findings, few well-designed studies, and significant methodological limitations, e.g. small sample sizes, lack of comparison groups and few adapted/validated measurement tools. In Kenya, HIV and ageing is an emergent subject, and little is known about the burden and determinants of these impairments. To address some of these research gaps, this PhD thesis sets out to: (a) Understand the health challenges faced by OALWH and the coping strategies they use to confront these challenges on the Kenyan coast, (b) Document the burden and associated factors of common mental disorders (CMDs) and frailty among OALWH compared to their HIV-uninfected peers on the Kenyan coast, (c) Examine the acceptability, reliability, and validity of a local (Swahili) measure of cognitive function, the Oxford Cognitive Screen Plus (OCSPlus), among older adults and provide a preliminary understanding of their cognitive performance (by HIV status) and associated factors. v Methodology: We used a mixed methods research design to answer our research questions, employing both qualitative and quantitative approaches. The qualitative phase of the study recruited 34 OALWH receiving routine HIV care and treatment, together with their healthcare providers (n=11) and primary caregivers (n=11). Qualitative data were drawn from semi-structured in-depth interviews that were audio-recorded, transcribed verbatim, and analyzed using the framework approach. Data management was done in Nvivo software. The quantitative phase, a cross-sectional survey, involved 440 older adults aged ≥50 years (58% OALWH). Locally adapted and/or validated tools were used to assess CMDs, frailty and cognitive function. All quantitative analyses were conducted using STATA software. Proportions were used to estimate the prevalence of CMDs and frailty among OALWH and their HIV-uninfected peers. Logistic regression was used to examine the factors associated with CMDs and frailty. Different psychometric tests were used to assess the reliability and validity of the OCSPlus tool. Test-retest reliability was evaluated using intra-class correlations. We computed Pearson correlation coefficients to assess convergent validity between OCSPlus and conventional cognitive tests. Multiple linear regressions were used to examine correlates of cognitive function. Results: Our findings from the qualitative phase showed that OALWH face multiple mental health challenges (e.g. symptoms of depression, anxiety, cognitive complaints) and physical health challenges (e.g. hypertension, diabetes, ulcers, somatic symptoms, and functional impairments), which were often complicated by a host of psychosocial challenges including food insecurity, ageism, HIV-related stigma, loneliness, and financial difficulties. Many of the perceived risk factors for these challenges were observed to overlap across the three health domains. Five major themes emerged from analyzing participants’ narratives on coping strategies, including self-care, positive religiosity, social connectedness, generativity and identity and mastery. Our findings also revealed maladaptive coping strategies, including self-isolation, over-reliance on over-the-counter medication, delayed healthcare seeking and skipping meals and medications. In the cross-sectional dataset, we found no significant differences in the vi prevalence of mild depressive symptoms (24% vs 18%) and anxiety symptoms (12% vs 7%) among OALWH compared to their uninfected peers, respectively. However, the prevalence of frailty was significantly higher among OALWH (24%) than their uninfected peers (13%). After adjusting for biopsychosocial factors, HIV seropositivity was not independently associated with CMDs or frailty. In multivariable analyses, the factors associated with increased odds of CMDs and frailty included HIV-related stigma, ageism, loneliness, functional impairment, sleeping difficulties, increasing household HIV burden, chronic fatigue, increasing medication burden, advanced age (>70 years), higher waist/hip ratio, visiting traditional healers, history of combination antiretroviral therapy (cART) regimen change/interruption, and prolonged illness following HIV diagnosis. In contrast, factors associated with reduced odds of CMDs and frailty included easier access to an HIV clinic, residing in larger households, higher household income, having a social network of friends, and being physically active. Most of these factors were corroborated in the qualitative phase of the study. In our last objective, the OCSPlus measure was found to be acceptable, reliable, and valid. Concerning cognitive performance, OALWH presented with significantly lower mean scores on language and executive function compared to their uninfected peers; however, they (OALWH) performed significantly better on memory. Several factors ranging from behavioural and lifestyle, sociodemographic, medical or treatment factors and psychosocial factors were significantly associated with cognitive performance (using OCSPlus). Discussion: Due to effective antiretroviral therapy (ART), people living with HIV are ageing, and this is witnessed across the world wherever ART is readily available. While this represents the success of HIV care and treatment, those ageing with HIV confront numerous health challenges, some of which are unique to this population, as observed in this study. Older adults living with HIV on the Kenyan coast are vulnerable to mental, cognitive, and functional health challenges, which appear to be complicated by several psychosocial challenges. Despite the observed health challenges, OALWH are able to integrate several positive strategies to promote or address their mental health and well- being. The findings of this study are timely in addressing some of the existing gaps in vii understanding the mental, cognitive, and functional health of OALWH in the country and set the stage for further research and the development of relevant interventions and healthcare strategies to improve the care of these adults. OALWH need to be recognized as an unique subpopulation requiring targeted health and social services, given the unique health challenges observed in this study. Relatedly, there is a need to build the capacity of healthcare providers, for instance, in the screening and management of CMDs and frailty, at least for the OALWH at risk of poor health outcomes, e.g., those facing multiple psychosocial challenges and deteriorating HIV treatment indicators. The majority of healthcare providers interviewed in the qualitative phase lamented their lack of skills and capacity to screen and manage CMDs and cognitive impairments. Additional support may include helping OALWH and their caregivers to mobilize social support and referrals, where possible, to relevant institutions and increase access to basic needs and services. The Kenya HIV prevention and treatment guidelines also need to be updated to highlight the unique needs of OALWH, e.g. multimorbidity. Different models of care have been recommended for the care of OALWH, including comprehensive geriatric assessment and integration of chronic care services into routine HIV care services. Formative work can be conducted to assess the possibility of introducing these models into care. Future work needs to ascertain the cause-and-effect association of the reported correlates and carry out formative work on the feasibility of multicomponent psychological and physical interventions to address identified health problems, e.g. psychosocial challenges, CMDs and frailty.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Public Health, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; HIV; Psychological and Functional Wellbeing; Kenyan coast; SDG-3: Good health and well-being